Предмет: Алгебра,
автор: German511
Разложите алгебраическое выражение на множители
2x(3степень)+6x(3степень)-3x-9
x(3степень)-7x(2степень)-3x+21
Ответы
Автор ответа:
0
1)думаю в 1выражении 6х во второй степени тогда:
=2х^2(х+3)-3(х+3)=(2х^2-3)(х+3)
2) х^2(х-7)-3(х-7)=(х^2-3)(х-7)
=2х^2(х+3)-3(х+3)=(2х^2-3)(х+3)
2) х^2(х-7)-3(х-7)=(х^2-3)(х-7)
Похожие вопросы
Предмет: Математика,
автор: maratoverasyl7
Предмет: Математика,
автор: msapoleva
Предмет: Математика,
автор: Аноним
Предмет: Химия,
автор: gaara1997
Предмет: Биология,
автор: iraberdnikova